6+8x=5x+9

Simple and best practice solution for 6+8x=5x+9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 6+8x=5x+9 equation:


Simplifying
6 + 8x = 5x + 9

Reorder the terms:
6 + 8x = 9 + 5x

Solving
6 + 8x = 9 + 5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-5x' to each side of the equation.
6 + 8x + -5x = 9 + 5x + -5x

Combine like terms: 8x + -5x = 3x
6 + 3x = 9 + 5x + -5x

Combine like terms: 5x + -5x = 0
6 + 3x = 9 + 0
6 + 3x = 9

Add '-6' to each side of the equation.
6 + -6 + 3x = 9 + -6

Combine like terms: 6 + -6 = 0
0 + 3x = 9 + -6
3x = 9 + -6

Combine like terms: 9 + -6 = 3
3x = 3

Divide each side by '3'.
x = 1

Simplifying
x = 1

See similar equations:

| 4ln(x+2)+3ln(4x+9)= | | 4[2(x-3)]= | | 7y+y(6-8)= | | 3x+x=1.35 | | 40-n=4n+7 | | 3x+x=135 | | 7(x-1)=6x+1 | | X^2-13x+60=90 | | 88=2+2(8-5x) | | 8x+6=5x+5 | | g-4=-3 | | 22=x^2 | | (-x^5/2)^4 | | m-9=3 | | y=1.2+0.8(-2) | | ln(x)+ln(5x)=9 | | -89=x+75 | | 9y-5y(6-8)= | | 12+6(z+2)=5z+2 | | pt+51=76 | | 7y+y(2-8)= | | 6-4x^5=4-3x^2 | | (6+x)(x)=28 | | 6-4x*5=4-3x*2 | | h+9=-45 | | 6+x(x)=28 | | -16t^2-120t+500=700 | | -19n+16=-18n-5 | | 43x=86 | | -19n+16=-18-5 | | 24+10x-x^2=p-(x-5)2 | | 15+6y=15y-3 |

Equations solver categories